A carbon dots-based fluorescent probe for turn-on sensing of ampicillin. (January 2020) - Fu, Yanzhao; Zhao, Shaojing; Wu, Shuilin; Huang, Li; Xu, Ting; Xing, Xuejian; Lan, Minhuan; Song, Xiangzhi
Abstract: Carbon dots (CDs) with blue fluorescence were synthesized through hydrothermal treatment of p -dihydroxybenzene and hydrazine hydrate. The fluorescence of the investigated CDs could be selectively quenched by iron ions (Fe 3+ ) because of the strong metal-ligand coordination and electrostatic interactions between the large amount of hydroxyl, amino, and carboxyl groups on CDs' surface and Fe 3+ . Interestingly, this non-fluorescent CDs + Fe 3+ complex displayed a sensitive and selective turn-on fluorescence toward ampicillin with a limit of detection of 0.70 μM. The sensing process could be observed by naked eyes under the 365 nm UV light irradiation. Importantly, CDs + Fe 3+ complex had been successfully applied in the detection of ampicillin in river water. Highlights: Fluorescent CDs were synthesized through hydrothermal treatment of p -dihydroxybenzene and hydrazine hydrate. The fluorescence of CDs was quenched significantly and quickly upon addition of Fe 3+ . The quenched fluorescence of CDs could be selectively turned on by the addition of ampicillin. The CDs-Fe 3+ system was successfully applied in the ampicillin detection in river water.